Penyusunan Rancangan Sistem Manajemen Berbasis Kompetensi Dalam Konteks Kualitas Kehidupan Kerja - Widya Satriyo Nugroho; Verina Halim Secapramana; V. Heru Hariyanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
Quality of work-life was a perspective which highlights the importance of balancing employees’ productivity and experience in the workplace to support organizational’s goals achievement. Pre-assessment survey at PT. X indicated competency development dimension as organization’s focus to improve employee quality of work-life. Employee competency development in quality of work-life context could be achieved by implementing performance management system which considering work result and work behavior (competency). Aim of this research was to evaluate PT. X’s performance management system, and designing performance management system procedures which aligned with quality of work-life context. This research used research and development phase one approach. Assessment result indicated that PT. X requires development on work procedures in order to implement competency based performance management system. Researcher then design 11 performance management system procedures related to competency aspect. Expert judgement result on those procedures indicated that procedures design were appropriate and ready to be implemented.